2017
DOI: 10.1038/jp.2016.277
|View full text |Cite
|
Sign up to set email alerts
|

Inter-center variation in death or tracheostomy placement in infants with severe bronchopulmonary dysplasia

Abstract: ICV in D/T is apparent among infants with sBPD. These results highlight that the indications for tracheostomy (and subsequent chronic ventilation) remain uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 20 publications
4
52
0
1
Order By: Relevance
“…This result corroborates previously published results, which also show it to be the most common indication for neonatal tracheostomy . Indeed, approximately 20% of infants with BPD who are referred to regional neonatal intensive care units die or receive a tracheostomy before discharge from the neonatal intensive care unit . Currently, no uniform indications for tracheostomy in this specific population exist, despite a recent publication from the interdisciplinary Bronchopulmonary Dysplasia Collaborative …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result corroborates previously published results, which also show it to be the most common indication for neonatal tracheostomy . Indeed, approximately 20% of infants with BPD who are referred to regional neonatal intensive care units die or receive a tracheostomy before discharge from the neonatal intensive care unit . Currently, no uniform indications for tracheostomy in this specific population exist, despite a recent publication from the interdisciplinary Bronchopulmonary Dysplasia Collaborative …”
Section: Discussionsupporting
confidence: 89%
“…[18][19][20] Indeed, approximately 20% of infants with BPD who are referred to regional neonatal intensive care units die or receive a tracheostomy before discharge from the neonatal intensive care unit. 21,22 Currently, no uniform indications for tracheostomy in this specific population exist, despite a recent publication from the interdisciplinary Bronchopulmonary Dysplasia Collaborative. 22,23 There are multiple limitations in using the ACS-NSQIP-P. Mortality and morbidity rates of patients after 30 days are not captured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandy et al reported a mean PMA of 51 weeks, while Murthy et al and Cheng et al reported mean PMAs of 46 weeks and 49 weeks, respectively. 1,14,15 We acknowledge that our PMA at time of tracheostomy is earlier than what is reported in the literature. A consensus practice within our multidisciplinary team caring for these infants is based on the large multicenter retrospective study from the NICHD NRN that included infants born at less than 30 weeks' gestation from 2001 to 2011, 304 of 8683 (3.5%) infants required tracheostomy.…”
Section: Discussionmentioning
confidence: 67%
“…Finally, there was a limited response regarding the practice of tracheostomy, and no unit offered a guideline covering their practice. There are recognised variations regarding timing and practice around this, but outcomes appear to justify tracheostomy use for ongoing respiratory support …”
Section: Discussionmentioning
confidence: 99%